(untitled) (Modern Problems of Metallurgy, 2022)
The article analyzes the change in the sulfur content of cast iron and the composition of slag in the technological chain of preparing cast iron for converter smelting. On the basis of the results of the conducted research, technical solutions and technological techniques aimed at eliminating cast iron resulfurization were developed and recommended. Spot probe scanning of bucket slag samples showed that in the slag phase, along with CaO∙SiO2∙Al2O3 type systems with different ratios of components containing 0.2–3.5% sulfur, CaxSiyAlz type systems containing up to 1% sulfur were found; in "beads" the sulfur content varies no more than 0.1 - 0.85% and in the form of sulfides of the (Fe, Mn)S type, mainly MnS, and in the non-metallic inclusions of "beads" the sulfur content is no more than 15 - 30%. Studies of the compositions of dry, friable and liquid glassy ladle slags after desulfurization showed that they do not change the phase composition, but unlike the original ladle slags, in the slag phase of such slags there are mainly CaO·SiO2·Al2O3·MgO type systems, enriched with magnesium oxides with variable ratio of components. At the same time, sulfur in the slag phase of dry slags is mainly in the form of (Ca, Mn, Mg, Al, Si)S complexes, and in the slag phase of liquid slags it is mainly in the form of MnS and less often in the form of (Ca, Mn)S complexes. According to the results of industrial experiments carried out at a number of enterprises in Ukraine and China, it was established that in order to limit the introduction of sulfur into converter steel with slag at the level of ≤0.002%, the remaining ladle slag after desulfurization should not exceed 0.5-0.7 kg/t of cast iron.